(3GdYed HGdCSWQdGHH GdcQi (B( (3dcd YQV aj GdfLhe (B)s - (3MGeO Hf Ydj GdhGSWj, CHh QHjYs
(3ChdgG (B:s
(3cjajI GdYed HGdCSWQdGH GdcQi dcd YQV hajg CHhGH GdHGH GdChd ai EXgGQ aVd gPG GdCSWQdGH Ydi ZjQg ef GdCSWQdGHGJ s
(3BNQgG (B:s
(3ai Ci ehVY JhGai GdTeS NW fUa GdfgGQ ai Gdjhe NeS eQGJ hPdc ai YQV agPg LedI cGajI ddYed HgPg GdCOdI Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fSNI NRGFfjIs
(3cJHJ HNW eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B398 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(350( 2)) s
Keywords: (3Gdadcs